STRATEGY OF TEACHER’S TPACK COMPETENCIES IN ECONOMICS EDUCATION - Kurniawati, Susanti; Maulana, Cepri; Ardiansyah, Hamdan (UNIVERSITAS NEGERI SURABAYA, 2025)
The urgency of this research is motivated by the urgent need for teachers' Technological Pedagogical Content Knowledge competency related to the rapid advancement of information technology, which affects the efficiency and effectiveness of the learning process and the development of student characteristics holistically. Therefore, this study aims to develop the TPACK-IDD IRR method to improve teachers' TPACK competency and evaluate the contribution of this method in improving each TPACK domain. The research method is design based research, focusing on the design, development, and evaluation of educational interventions. The stages of model development are applied to the ADDIE development model. The implementation of TPACK IDD IRR consists of the stages of Introduction, Demonstration, Development, Implementation, Reflection, and Revision. The sample size consists of 120 pre-service teachers in the field of economics. Data collection techniques by observation and survey with observation guide instruments and questionnaires. The collected data were analyzed with descriptive statistics. The effectiveness of the model uses a one-sample t-test to identify differences in TPACK domain scores before and after the implementation of the IDD IRR strategy. The results of the study indicate that the IDD IRR model, which integrates discussion, simulation, and project-based learning methods, positively influences the TPACK competency of economics teachers. Ultimately, this study concludes that the IDD IRR strategy effectively enhances the TPACK competency of prospective economics educators, preparing them to face the challenges of modern teaching.